A model for information support for knowledge workers - Justyna Patalas-Maliszewska (Foundations of Management, 2014)
This article aims to elaborate on a model of information support for knowledge workers in Polish enterprises. Earlier research has explored the use of Web 2.0 technology for information sharing. Nevertheless, relatively little information has been published that focuses on the impact of information sharing among knowledge workers within a company and its subsequent influence on a firm's effectiveness as identified via the number of new products created, number of completed research topics, or number of new patents. The author aims to analyze the effectiveness of information sharing in Polish enterprises based on the research results gained from the study described in this paper. In particular, this study pays attention to the likely consequences and results of information sharing by the use of employee web logs. This is followed by a discussion of the results of the empirical studies and of the supporting literature. The summary indicates potential directions for further work.
Keywords: 650; knowledge workers; employee web logs; information sharing